An Approach to Estimate the Parameters of Von Bertalanffy Growth Models in forestry - Borah, Munindra; Mahanta, Dimpal Jyoti (Indian Forester, 2018)
In this paper an attempt has been made to introduce a few methods of estimation to fit the von Bertalanffy growth model in forestry viewpoint. Integral forms of the von Bertalanffy growth model has also been discussed together with their varied re-parameterizations. A brief study on the basic properties of the parameters of the model has been made. Fitting of the von Bertalanffy model usually involves some traditional nonlinear optimization methods, which requires a large amount of computation. Here, certain methods of estimation have been introduced to suit the models, which demands less computation and can be used for any growth data. The maximum diameter data and top height growth of babul (Acacia nilotica) tree and the top height age, the cumulative basal area production and the mean diameter at breast height data, originated from the Bowmont Norway spruce thinning experiment, sample plot 3661 are used for testing the validity of the methods. The data of babul are based on the analysis of sample plot data of Uttar Pradesh, Maharashtra and Madhya Pradesh. Results show that each method, introduced in this paper performed well. The estimated parameters are logically and biologically significant.